The Correlation of Social Support, tolerance and Mental Health in Children of Martyrs and war-disabled in Universities of Ilam - S. azadi; H. Azad (Afarand Scholarly Publishing Institute, 2011)
Introduction: Mental health -as one of the two primary elements of health- is a requirement for a effective, positive and pleasant life. Also mental health of people in a society, especially that of the effective groups, is necessary for the dynamism and development of the society. The primary role of university students as future's managers in every society shows the necessity of ensuring their mental health, finding and eliminating the negative elements affecting the mental health. Goal: This research has been done to investigate the Correlation of Social Support tolerance and Mental Health. Material: The subjects were 1233 Children of Martyrs and war-disabled in Universities of Ilam (338 students of Associate's Degree : 27.41 percent, 895 students of B.A :72.58 percent . Using KORJSI AND MORGAN, 297 students were selected unintentionally and filled in the questionnaire of GOLDBERG and HILYER'S (1997) TOLERANCE AND PHILIP'S SOCIAL SUPPORT. For analyzing the results, in addition to descriptive variables, one way variance analysis, T-TEST AND structural equation modeling WERE USED. Results: Findings in this research indicate a significant relationship between Social Support and Mental Health (0.333), Social Support and tolerance (0.331) and also tolerance and mental health (0323). In this regard, social support of other important people in life (0.67), social support of the family (0.56), social support of friends (0.42) have the most significant relationship with mental health. Also in the step by step regression model, social support 0.411, social support and tolerance 0.614 predict mental health variance. Also, In structural equation modeling , the direct effect of support on health is 0.411, the indirect effect of support on health is 0.42 and the direct effect of tolerance on health is 0.15. Discussion and Conclusion: Social support is one of the most powerful predictors of mental health, in a sense that the more extended social network support the person has, the more mentally healthy he is. Vaccinating the individuals against stressful situations before happening, social support reduces the rate of mental stress. On the other hand, tolerance is a factor which enhances the rate of life satisfaction since it reduces individualchr('39')s negative emotions and increases the mental health rate. Also tolerance is defined as a resource to overcome the difficulties in life more easily, to resist against stress and eliminating their psychological effects. Findings in this research, parallel to other researches, indicate that people with high levels of tolerance, keep their psychological health in stressful and tough situations and enjoy psychological adaptation.